2018
DOI: 10.1002/anie.201711575
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Linear and Branched Alkanes Using Host–Guest Complexation of Cyclic and Branched Alkane Vapors by Crystal State Pillar[6]arene

Abstract: Activated crystals of pillar[6]arene produced by removing the solvent upon heating were able to take up branched and cyclic alkane vapors as a consequence of their gate-opening behavior. The uptake of branched and cyclic alkane vapors by the activated crystals of pillar[6]arene induced a crystal transformation to form one-dimensional channel structures. However, the activated crystals of pillar[6]arene hardly took up linear alkane vapors because the cavity size of pillar[6]arene is too large to form stable com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 28 publications
2
107
0
1
Order By: Relevance
“…Afterward, the separation of branched alkanes from a mixture of linear and branched alkanes using NACs of 30 to improve research octane numbers (RONs) was achieved by Ogoshi et al In addition, we found that NACs of both 29 and 30 can be used to separate cyclic aliphatics from corresponding aromatics . Crystals of 29a separate toluene from methylcyclohexane with a purity of 98.8%, while 30b crystals separate methylcyclohexane from toluene with a purity of 99.2% ( Figure ).…”
Section: Pillararene‐based Comsmentioning
confidence: 85%
“…Afterward, the separation of branched alkanes from a mixture of linear and branched alkanes using NACs of 30 to improve research octane numbers (RONs) was achieved by Ogoshi et al In addition, we found that NACs of both 29 and 30 can be used to separate cyclic aliphatics from corresponding aromatics . Crystals of 29a separate toluene from methylcyclohexane with a purity of 98.8%, while 30b crystals separate methylcyclohexane from toluene with a purity of 99.2% ( Figure ).…”
Section: Pillararene‐based Comsmentioning
confidence: 85%
“…We also showed that activated P5A crystals could be used for uptake and sensing of linear alkane vapors,, and separation of linear alkanes with various lengths . In addition, activated pillar[6]arene crystals can be used for isolation of branched alkanes to increase the octane number . However, to our knowledge, this is the first report to show that different molecular arrangements of P5As give rise to different patterns of the uptake, release, and molecular dynamics of the guest in the crystals.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Ogoshi and coworkers reported a crystal state pillar [6]arene (P6), which they synthesized to separate linear and branched alkanes. [17] Generally, quality of gasoline is evaluated by the research octane numbers (RON). In this work, they demonstrated that isolation of branched alkanes from a mixture of linear and branched alkanes using a vapor sorption material based on pillar [6]arene.…”
Section: Solid Materials Constructed From Pillar[n] Arenesmentioning
confidence: 99%
“…Moreover, according to their adaptive structure, pillar[n]arenes have been used as solid materials recently. [17][18][19] Thus in the third part of this paper, we will review some fascinating cases of selective separation, adsorption purification or sensing materials based on pillar[n] arenes in the solid state. The applications of pillar[n]arenes in advanced materials are not limited in these three fields.…”
Section: Introductionmentioning
confidence: 99%